2020
DOI: 10.1101/2020.08.20.258301
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exposing distinct subcortical components of the auditory brainstem response evoked by continuous naturalistic speech

Abstract: The auditory brainstem is important for processing speech, yet we have much to learn regarding the contributions of different subcortical structures. These deep neural generators respond quickly, making them difficult to study during dynamic, ongoing speech. Recently developed techniques have paved the way to use natural speech stimuli, but the auditory brainstem responses (ABRs) they provide are temporally broad and thus have ambiguous neural sources. Here we describe a new method that uses re-synthesized "pe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 60 publications
4
13
0
Order By: Relevance
“…Our findings extend this work into a higher frequency range and into the realm of spectro-temporally complex speech sounds. More recent work, conducted in parallel with studies reported here, has used a similar deconvolution approach to calculate the F0 response from continuous speech (Polonenko and Maddox, 2021). In line with our findings, they also identified F0 responses that are consistent with the notion of resulting from a sequential activation of generators along the ascending auditory pathway.…”
Section: F0 Responses Compress Ffrs Into a Meaningful Formatsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings extend this work into a higher frequency range and into the realm of spectro-temporally complex speech sounds. More recent work, conducted in parallel with studies reported here, has used a similar deconvolution approach to calculate the F0 response from continuous speech (Polonenko and Maddox, 2021). In line with our findings, they also identified F0 responses that are consistent with the notion of resulting from a sequential activation of generators along the ascending auditory pathway.…”
Section: F0 Responses Compress Ffrs Into a Meaningful Formatsupporting
confidence: 89%
“…Furthermore, it should be possible to compute the underlying F0 responses by inverting the convolution operation. So-called 'deconvolution' approaches have successfully been used in a wide range of neuroscientific applications (Aquino et al, 2014;Teichert and Ferrera, 2015), including the closely related 40 Hz auditory steady state response (Bohórquez and Özdamar, 2008) and continuous speech (Maddox and Lee, 2018;Polonenko and Maddox, 2021). To date, however, deconvolution has never been used to recover the F0 response underlying FFRs to stimuli with time-varying pitch.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the spoken stories used here are intrinsically motivating to a listener, reflecting such everyday listening situations (Dunlop and Walker, 2013). Our work shows, in line with recent studies (Broderick et al, 2018(Broderick et al, , 2019(Broderick et al, , 2021Brodbeck et al, 2020;Erb et al, 2020;Polonenko and Maddox, 2021), that utilizing naturalistic, spoken stories to investigate speech listening provide a useful avenue to investigate listening in ecologically valid conditions.…”
Section: Using Narratives To Approximate Realistic Listening Scenariossupporting
confidence: 87%
“…Recent studies using non-invasive electrophysiology have shown that auditory activity at putative subcortical processing stages can be measured for complex natural sounds (such as speech; [19][20][21][22]. Furthermore, this subcortical activity can even be modulated by attention (19,20,23).…”
Section: Modelling Of Subcortical Activity Reveals a Predominant Tracking Of The Modulation Rate Of Speechmentioning
confidence: 99%